Participatory Budgeting and the Use of Information and Communication Technologies: A Virtuous Cycle? - Cunha, Eleonora S. M. (2011)
This text discusses whether the use of Information and Communication Technologies (ICT) in Participatory Budgeting processes can promote more engaged forms of citizenship and democracy. The discussion is based on the analysis of a few examples from different countries, which show how the use of ICTs is framed by institutions. The inclusion of ICT in participation and decision-making processes can assume very different shapes. In some cases, they can be used within well-defined limits, as information tools or for monitoring the PB during the debate and the implementation phase; in other cases, a more advanced use of ICT potentialities can serve as support to political decision-making processes. The different examples presented in the text represent the different configurations that exist in the ambit of both “subordinate” and “coordinated” models of ICT use within democratic processes.